2019
DOI: 10.1530/eje-19-0058
|View full text |Cite
|
Sign up to set email alerts
|

Use of radiotherapy after pituitary surgery for non-functioning pituitary adenomas

Abstract: Surgery is the treatment of choice for non-functioning pituitary macroadenomas (NFPAs). In cases of postoperative remnant growth or tumor recurrence, radiotherapy (RT) can be considered. The role of RT in the postoperative management of NFPAs is still debated. The main arguments against routine use of RT are the lack of randomized controlled trials, the use of clinically irrelevant endpoints in most studies on RT, the benign character of the condition, the potential for side effects of RT, and the option to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 106 publications
2
20
0
3
Order By: Relevance
“…If we consider regrowth after treatment as the first hallmark of aggressiveness, several studies show that approximately 20-50% of patients with a nonfunctioning adenoma display signs of regrowth five years after initial surgery [9,20]; this number is lower if additional radiotherapy is applied [20]. After ten years, the percentage of patients with a regrowth of the adenoma is >50% [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If we consider regrowth after treatment as the first hallmark of aggressiveness, several studies show that approximately 20-50% of patients with a nonfunctioning adenoma display signs of regrowth five years after initial surgery [9,20]; this number is lower if additional radiotherapy is applied [20]. After ten years, the percentage of patients with a regrowth of the adenoma is >50% [20].…”
mentioning
confidence: 99%
“…If we consider regrowth after treatment as the first hallmark of aggressiveness, several studies show that approximately 20-50% of patients with a nonfunctioning adenoma display signs of regrowth five years after initial surgery [9,20]; this number is lower if additional radiotherapy is applied [20]. After ten years, the percentage of patients with a regrowth of the adenoma is >50% [20]. In series on hormone secreting adenomas, the recurrence risk is lower after medical treatment or surgery, but it needs to be acknowledged that in prolactinomas [21], acromegaly [22] and Cushing's disease [23][24][25] the tumor size at detection and treatment is smaller compared to nonfunctioning adenomas.…”
mentioning
confidence: 99%
“…At 15 years post-operatively, mean PFS was calculated as 93% after RT compared to 33% if no RT was administered (Gittoes et al 1998). However, there are no randomised controlled trials indicating the superiority of adjuvant post-operative RT compared to active surveillance, while the potential side-effects of RT render the indication for RT debatable (Chanson et al 2019). Furthermore, a recent meta-analysis reported that residual tumour growth occurs slowly as the tumour doubling time is only 3.4 years with no growth observed during follow-up in 50-60% of patients (Chen et al 2012).…”
Section: Management Of Recurrent Tumoursmentioning
confidence: 99%
“…Certainly, unless the tumour exhibits especial aggressiveness radiologically and/or histopathologically, we believe RT should be reserved for the time of disease progression during follow-up, while immediate post-operative treatment should be reserved for cases with significant tumour remnant and high risk of progression (Lucas et al 2016). Furthermore, adjuvant RT should be considered for patients presenting with aggressive NFpitNENs, large tumours with suprasellar extension or cavernous sinus invasion or displaying aggressive histopathological characteristics such as a LI Ki-67 >3% or extensive immunostaining for p53 (Chanson et al 2019). RT may also be used as primary treatment in cases where surgery is not feasible.…”
Section: Management Of Recurrent Tumoursmentioning
confidence: 99%
See 1 more Smart Citation